Filgotinib induction-study baseline characteristics of patients with ulcerative colitis who achieve sustained corticosteroid-free remission: analysis of the phase 2b/3 SELECTION study - Taku Kobayashi; Axel Dignass; Xavier Roblin; Yoshie Takatori; Toshihiko Kaise; Alessandra Oortwijn; Corinne Jamoul; Toshifumi Hibi (Intestinal Research)
Background/Aims Obtaining and maintaining corticosteroid-free remission are important goals of treatment for ulcerative colitis (UC). Characteristics associated with achieving corticosteroid-free remission were assessed in filgotinib-treated patients in SELECTION, a 58-week, phase 2b/3 trial in moderately to severely active UC. Methods This post hoc analysis used data from filgotinib-treated patients receiving corticosteroids at maintenance baseline in SELECTION. Univariate logistic regression was performed to assess induction baseline characteristics associated with 6 months of corticosteroid-free remission at week 58, defined as clinical remission without using corticosteroids for at least 6 months. Results At maintenance baseline, 92 and 81 patients were receiving corticosteroids in the filgotinib 200 mg and filgotinib 100 mg groups, respectively. Age, body mass index, history of pancolitis, disease duration, fecal calprotectin levels, C-reactive protein levels, Mayo Clinic Score, concomitant corticosteroids, immunomodulators, and aminosalicylates had no statistically significant effect on the likelihood of achieving corticosteroid-free remission. Baseline characteristics associated with increased odds of corticosteroid-free remission were Mayo Clinic Endoscopic Subscore of 2 (vs. 3) in the filgotinib 200 mg and filgotinib 100 mg groups, and female (vs. male) sex, current (vs. former or never) smoking, and being biologic‑naive (vs. experienced) in the filgotinib 200 mg group. Conclusions Steroid tapering can be achieved in patients with UC receiving filgotinib 200 mg independently of baseline characteristics such as clinical activity and duration of illness. However, the likelihood of achieving corticosteroid-free remission was higher among patients who were biologic-naive, current smokers, had low endoscopic inflammatory burden and who were female.